Current use of medicinal plants for children’s diseases among mothers in Southern Romania - Petran, Madalina; Dragoș, Dorin; Stoian, Irina; Vlad, Adelina; Gilca, Marilena (Frontiers in Pharmacology, 2024)
There is a limited number of studies focusing on ethnomedical practices in children, particularly in Eastern Europe. Romania has a rich history of using medicinal plants in ethnopediatric care, and our objective was to identify the medicinal plants currently employed in treating childhood illnesses in the southern region of the country. Material and methods: Our investigation used structured interviews, focusing on respondent demographics, local names of therapeutically employed herbs, the specific plant part(s) utilized, methods of preparation and administration, and local folk indications of taxa. A total of 326 mothers with children aged 0 to 18, hospitalized in the "Grigore Alexandrescu" Children Emergency Hospital Bucharest and residing in Southern Romania, were enrolled in the study. Use Value Citation Index (UVc), Informant Consensus Factor (Fic), and Fidelity Level (FL) were calculated. Results: Twenty-five plants were identified for treating children's diseases in Southern Romania. The majority of informants resided in urban areas, and mothers primarily acquired knowledge from family members and healthcare professionals. The herbs most frequently employed were Mentha spp. (UV= 0.509) for diarrhea, Matricaria spp. (UV= 0.301) for skin infections (Fic = 0.99) and digestive diseases (Fic = 0.98), and Calendula officinalis L. (UV=0.365) for skin diseases (Fic = 0.99). Less utilized were Raphanus raphanistrum subsp. sativus (L.) Domin in respiratory diseases, Prunus avium (L.) L. stalks in urinary tract ailments, Helianthus annuus L. in ear infections, Allium sativum L. in intestinal parasitosis, Viola tricolor L. in hives, Triticum aestivum L. in dermatitis and Allium ursinum L. as a tonic. In 184 cases herbal treatment was used in conjunction with conventional medications. Education level correlated with the number of employed plants and the variety of treated ailments, while residency (rural vs. urban) did not. Both residency and education influenced plant procurement methods: rural background and, surprisingly, higher education were linked to a preference for harvesting rather than purchasing plants. Conclusions: Botanical remedies are still commonly used in the treatment of pediatric diseases in Southern Romania, although the variety of taxa seems reduced compared to the past. Further exploration is essential to unlock the maximum benefits of ethnopediatric practices.